Pelayanan Poli Umum Puskesmas Jatibening Baru Kecamatan Pondokgede Kota Bekasi - Andika Wicaksono, Nabil; Santoso, R. Slamet; Subowo, Ari (Journal of Public Policy and Management Review, 2024)
Health is a basic human need. Therefore, the government has an obligation to fulfill the needs of public health services. One form of government effort in providing quality health services to the community is through the Community Health Center (Puskesmas). However, the services provided by Puskesmas still have various problems, namely there are still many community complaints related to infrastructure facilities at Puskesmas, timeliness of services, and the attitudes and behavior of Puskesmas officers. In this case, some facts in the field found that the Jatibening Baru Health Center still does not have binding regulations related to the implementation of quality services. This study analyzes the quality of service of the Jatibening Baru Puskesmas, especially in the General & Elderly Poly Service, using conclusions from service quality theories derived from Zeithaml, Pasaruman, and Berry and analyzes factors that hinder service quality using conclusions from the theory of factors affecting service quality derived from Moenir using a qualitative descriptive approach. The data collection techniques used were observation, documentation, and interviews. The results showed that the quality of the Jatibening Baru Health Center was still not optimal in the dimensions of tangible, reliability, responsiveness, and assurance. This condition is motivated by several factors that still hamper related to awareness factors, organizational factors, income factors, ability and skill factors, and service facility factors. Researchers provide recommendations to answer the research problems that have been analyzed, namely by improving the dimensions that are still not optimal.